Optimalisasi Edukasi Bahaya Pernikahan Usia Anak dalam Upaya Cegah Stunting Sejak Dini pada Remaja - Jauhari, M. Thonthowi; Efendi, Saparudin; Ardian, Junendri; Isasih, Widani Darma; Kusuma, Wirajaya; Haryono, Haryono (Forum Kerjasama Pendidikan Tinggi, 2026)
Child marriage is one of the major risk factors contributing to the high prevalence of stunting in Indonesia, particularly in rural areas. Adolescents, as a group transitioning into adulthood, play a strategic role in preventing early marriage through improved literacy in reproductive health and nutrition. This community service program aimed to enhance the knowledge and awareness of youth members of the Karang Taruna in Sukaraja Village regarding the dangers of child marriage and its association with stunting risk. The program involved 23 adolescents as participants. The implementation methods included initial observation, development of educational materials, coordination with village authorities, interactive lectures, participatory discussions, and demonstrations of educational media. Evaluation was conducted using pre-test and post-test instruments, attitude observation, and brief reflective interviews. Results showed a significant increase in participants’ knowledge, indicated by an improvement in the average score from 52.8 to 80.97 after the educational session. Participants also demonstrated more critical attitudes toward child marriage practices and expressed commitment to becoming agents of change in stunting prevention within their community. This program proved effective in improving adolescents’ reproductive health literacy and shows potential for sustainability through Karang Taruna initiatives to continue educational campaigns. Community-based education efforts such as this are essential to support the postponement of marriage age and reduce stunting risk among future generations.